A atuação da promoção de vendas em meios interativos (e-promotion) - Gadbem, Adriano de Almeida (2010)
The research proposal is based on the theme integrated communication of marketing through the approach of the action of communicative competence, sales promotion, on the internet and the emergence of e-promotion, as an extension of the point of sale message. The goal is to see how these new communication technologies, specifically the internet, are changing the way sales are promoted. The methodology to be applied in the project consists of a qualitative exploratory research through a concise bibliographic research that intends to investigate the many works related to the themes of communication, sales promotion, digital marketing and e-commerce, in the multiple case study of companies that use offline promotions and e-promotion as a communication tool. The conclusion pointed to hybrid actions and apparent absence of promotions that act in their entirety in the offline environment. (AU)